(untitled) (Economic and Political Thought, 2015)
The article provides a comparative analysis of the anthropological concept of the ‘shadow elites’, which has been introduced by a renowned anthropologists, Janine R. Wedel in her book published in 2009. The ‘shadow elites’ are informal, flexible networks that are formed on the intersection of business, government, media and science. Moreover, the development of shadow elites is characteristic of societies in relatively developed states and cannot be described simply as corruption or clientelism. In her book Wedel focuses on three examples: the Chubais clan in Russia, the Ordynacka Association in Poland and the Richard Perle neoconservative network in Washington. The author of this article accepts Wedel’s definition but argues that we still lack a comprehensive theory concerning the genesis of those elites. The author strives to propose such a theory and recommends further research. The author’s concept examines the global processes that disturb the balance between the three branches of powers in modern states. It is the author’s contention that the contemporary global political environment favors strong executives with little checks from other branches. The informal networks circling around the modern executives are, in turn, what constitutes the shadow elites. The process is observed world-wide, however, the pathologies typically found in post-communist states facilitate it. The author focuses especially on the cases related to the UE and Poland. The article among other examples describes the connections of the former Polish primeminister Kazimierz Marcinkiewicz and the networks of some the persons involved in the 2014 Polish wiretapping scandal.